Digital watermarking : related work - Khalifa, Othman Omran; Yusof, Yusnita (IIUM Press, 2011)
Digital watermarking is a huge research area which is progressively growing. It covers theoretical studies, novel techniques, attacks and performance analysis. Over the years, the digital watermarking community has focused on developing new techniques for watermark embedding and detection. Analysis of these techniques leads to methods for attacks and countermeasures which are used to discover faults and limitations in applications, encouraging the development of better ones. Digital watermarking is distinctive depending on its techniques and applications. In general, digital watermarking is distinguished according to media type (image, audio, video and etc.), visibility (visible and invisible), robustness level (fragile, semi-fragile and robust) and the need for original data (blind, semiblind and non-blind). This chapter consists of literature review and theoretical background. A general model of digital watermarking and its terminology were described as well. Third section concentrates on related work, as this area can be considered relatively new looking at when it started and the progress made so far